Microwave-Promoted Michael Addition of Azaheterocycles to α,β-Unsaturated Esters and Acid under Solvent-Free Conditions - Dubois, Lilian; Acher, Francine C.; McCort-Tranchepain, Isabelle (Synlett, 2012)
Regioselective Michael addition of N-9 adenine to ethyl acrylate under microwave activation in solid-liquid solvent-free phase-transfer catalysis using TBAB as catalyst and DABCO as base was extended to tert-butyl acrylate and acrylic acid. Under these conditions and in the presence of a catalytic amount of KOH, first Michael addition of indole and indolylmaleimide to acrylates is also reported.
Keywords: microwave irradiation; Michael addition; azaheterocycles; phase-transfer catalysis; green chemistry